Waqf commitment for higher education: does religious value matter? / Muhammad Adli Ahmad and Abdul Jabbar Abdullah. - Ahmad, Muhammad Adli; Abdullah, Abdul Jabbar (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
This paper discusses the importance of religious value in waqf commitment. We surveyed 323 respondents of the Kolej Poly-Tech MARA (KPTM) alumni to examine the relationship between religious value and waqf commitment for higher education. Although religious value is one of the important factors in donating and doing charity in literature, our study finds religious value has no significant relationship with waqf commitment. Meanwhile, factors such as personal characteristics, self-image, psychological benefits, personal satisfaction, trust and social norm are found to be significant.